Population Pharmacokinetics of Vancomycin in Postoperative Neurosurgical Patients. Issue 11 (3rd August 2015) - Li, Xingang; Wu, Yuanxing; Sun, Shusen; Mei, Shenghui; Wang, Jiaqing; Wang, Qiang; Zhao, Zhigang
<x xml:space="preserve">Abstract</x> Neurosurgical procedures may damage the blood–brain barrier to allow more vancomycin distribution into the cerebrospinal fluid (CSF) from blood after intravenous administration. However, a large intersubject variability in CSF vancomycin concentration was observed. We aimed to develop a population pharmacokinetic model to guide vancomycin dosing in patients after neurosurgical operation. Blood and CSF samples were collected and determined from postoperative neurosurgical patients after vancomycin administration. A three‐compartment (central, peripheral, and CSF) model was proposed to characterize the pharmacokinetics of vancomycin. A nonlinear mixed‐effects modeling approach was applied to fit the blood and CSF data simultaneously. The covariate analysis found that the CSF albumin level was strongly associated with the clearance between central and CSF compartment. Visual predictive check indicated that the proposed population pharmacokinetic model agrees well with the observed vancomycin concentrations. Individualized vancomycin dosage regimens could be developed for postoperative neurosurgical patients with different CSF albumin levels through model simulations. The CSF albumin level is a determinant of CSF vancomycin concentration. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:3960–3967, 2015